2012
DOI: 10.1007/s00264-012-1596-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of the mechanical axis of lower limb and body weight in the horizontal tear and root ligament tear of the posterior horn of the medial meniscus

Abstract: Purpose To compare and analyse the relationship between horizontal tear and root ligament tear of the posterior horn of the medial meniscus (PHMM) and the degree of varus in the axis of lower limb and body weight. Methods One hundred and nineteen patients underwent surgical treatment as they were diagnosed with medial meniscus tear in our hospital from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Plain radiographic examination of the knee under loading conditions is recommended when examining patients with meniscal tears [24]. Meniscal extrusion after an MMPRT often leads to radiographic changes, such as MJS narrowing and varus deformity of the knee [25]. We demonstrated that these intra-articular changes, caused by MMPRT, are measurable on the radiographic Rosenberg view (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Plain radiographic examination of the knee under loading conditions is recommended when examining patients with meniscal tears [24]. Meniscal extrusion after an MMPRT often leads to radiographic changes, such as MJS narrowing and varus deformity of the knee [25]. We demonstrated that these intra-articular changes, caused by MMPRT, are measurable on the radiographic Rosenberg view (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…The internal rotation of the tibia is influenced by the properties and activities of various muscles, including the popliteal muscle and the semitendinosus, semimembranosus, sartorius, and gracilis muscles. However, in a study evaluating the rotation of the tibia using upright weight-bearing computed tomography (CT) imaging, internal rotation of the tibiofemoral joint did not increase between 30°and 60°of knee flexion [25]. Therefore, considering the Rosenberg view is obtained with the knee in 45°of flexion, we infer that the internal rotation of the tibia during imaging was not influenced by the state of muscle contraction.…”
Section: Discussionmentioning
confidence: 91%
“…5 As a degenerated tear, horizontal tear is the most common type in medial meniscus tear. 6 Long-term abrasion and extrusion could lead to internal degeneration of meniscus, which moves back and forth between tibiofemoral articular surfaces. This movement causes the separation of the upper and lower articular surfaces of meniscus.…”
mentioning
confidence: 99%
“…To restore the physiological relationship between femur, meniscus and tibia, accurate positioning of the meniscus based on precise meniscal sizing is critical in meniscus repair and replacement [24]. Several variables, such as patient height and weight and radiographic measurements of the medial tibial plateau are considered good candidates for determining medial meniscal size [25]. Height has linear [15].…”
Section: Discussionmentioning
confidence: 99%